REDUKSI DERAU DENGAN MENGGUNAKAN TAPIS ADAPTIF - Kristiyana, Samuel (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
In signal processing, often contaminated by other signal that has bad influence or called by noise. Noise will lose by using adaptive filter with predict method. This filter needs two inputs that are contaminated signal with delayed input as main input which use as training input and the other contaminated signal with input as reference input, so result of error is the success process of reduction noise. This filter use LMS filter of algorithm value variable with adapted process filter. Adaptive filter with predict method tested by noise signal. This filter tested by kind of variable value and Î¼. So, we will get a point of value, total of optimal value and also the Î¼ optimal value.